Sustainable supply chain management - Bernon, Mike (Henry Stewart Talks, 2010)
Defining sustainable supply chain management, Defining sustainability, Humans and sustainability, Supply chains and sustainability, World green house gases by sector, Transport effects in the UK, Sustainability and the "triple bottom line", Sustainable supply chain management, Life cycle analysis, Food miles, Stewardship, Carbon trading and green taxes, Strategies for sustainable supply chain management, Competitive advantage, Transformational supply chain, Summary